Systematic screening for polymorphisms within the UGT1A6 gene in three Chinese populations and function prediction through structural modeling. (May 2009) - Xing, Yi; Yang, Lun; Wang, Lei; Shao, Liyan; Wei, Zhiyun; Xuan, Jiekun; Li, Jun; Qin, Shengying; Shu, Anli; He, Lin; Xing, Qinghe
Aims: To date, there have been relatively few studies on the UGT1A6 gene in the Chinese population. The present study was designed to determine the allele frequencies and haplotypes of this gene in the population and predict the candidate functional mutations.Materials & methods: We carried out the first systematic screening of polymorphisms of the gene in an SNP analysis involving 1074 Chinese subjects from three ethnic groups, namely Han, Dong and She, using direct sequencing. We identified the putative substrate binding pocket using a homology-modeled structure and produced a practical model for predicting the function of polymorphisms in UGT1A6 .Results: A total of six SNPs and 10 mutations were detected including nine known and seven novel ones. The novel mutations were 73G>A (V25I), 89T>G (L30R), 222A>C, 657C>A, 773A>T (D258V), 1040A>G (N347S) and 1467C>T. In addition, we detected, for the first time in the Chinese population, SNPs 105C>T, 627G>T as well as mutations 308C>A (S103X), IVS2+15T>C and 1088C>T (P363L). Strong linkage disequilibrium was observed among 19T>G, 315A>G, 541A>G and 552A>C. There were seven haplotypes whose frequencies were more than 0.01 in one or more of the three ethnic groups. P363L in the C-terminal domain might weaken the binding of cofactor UDPGA to the domain and induce a poor metabolism genotype of UGT1A6 .Conclusion: Our study suggests that genetic polymorphisms in UGT1A6 may contribute to interindividual and intra-ethnic differences. The results should prove helpful in the development of pharmacogenomics in China.